Compliance with neuromuscular training and anterior cruciate ligament injury risk reduction in female athletes: a meta-analysis - Sugimoto, D.; Myer, G. D.; Bush, H. M.; Klugman, M. F.; Medina McKeon, J. M.; Hewett, T. E. (Journal of Athletic Training, 2012)
Context: No consensus exists about the influence of compliance with neuromuscular training programs on reduction of the risk of anterior cruciate ligament (ACL) injury. Objective: To systematically review and synthesize the published literature to determine if compliance with neuromuscular training is associated with reduced incidence of ACL injury in young female athletes. Data Sources: We searched PubMed, SPORTDiscus, CINAHL, and MEDLINE for articles published from 1995 to 2010 using the key words anterior cruciate ligament prevention, ACL prevention, knee prevention, prospective knee prevention, neuromuscular training, and neuromuscular intervention. Study Selection: Criteria for inclusion required that (1) the number of ACL injuries was reported, (2) a neuromuscular training program was used, (3) females were included as participants, (4) the study design was prospective and controlled, and (5) compliance data for the neuromuscular training program were provided. Data Extraction: Extracted data included the number of ACL injuries, total number of participants per group, observation time period, number of participants who completed each session, number of sessions completed by an entire team, and number of total sessions. Attendance was calculated as the number of participants who completed each session converted into a percentage of the total number of participants. Intervention completion was calculated as the number of sessions completed by an entire team converted into a percentage of the total number of training sessions. These data were used to calculate an overall rate of compliance. Data Synthesis: Six of 205 identified studies were included. Incidence rates of ACL injury were lower in studies with high rates of compliance with neuromuscular training than in studies with low compliance rates (incidence rate ratio = 0.27 [95% confidence interval = 0.07, 0.80]). Tertile analysis indicated rates of ACL injury incidence were lower in studies with high compliance rates than in studies with moderate and low compliance rates (incidence rate ratio = 0.18 [95% confidence interval = 0.02, 0.77]). Conclusions: A potential inverse dose-response relationship exists between compliance with neuromuscular training and incidence of ACL injury. Attending and completing recommended neuromuscular sessions appears to be an important factor for preventing ACL injuries.